GEOPOLITICAL INTERESTS AND THE MAIN MEANS OF ITS IMPLEMENTATION IN THE POLITICS OF LEADING INTERNATIONAL ACTORS ON THE AFRICAN CONTINENT (Вісник: Міжнародні відносини, 2024)
The author made an attempt to comprehensively analyze the policies of the French Republic, the United States of America, the People's Republic of China, the Republic of India, and the Russian Federation with African countries and the reasons for the states' interest in deepening cooperation, in the place with the ways of their implementation. The main spheres of interaction between them are traced. Specific measures and projects taken by the specified states to intensify cooperation with African states were considered. Considerable attention is paid to the strategies of governments regarding the African continent.
Keywords: Africa, French Republic, United States of America, People's Republic of China, Republic of India, Russian Federation, Persian Gulf, geopolitics, economic projects, strategies, natural resources, competition